Training monitoring in elite triathletes - Stanley, J. (Science + Triathlon 2015 World Conference, 2015)
Elite triathletes undertake some of the highest training loads of any elite athlete. High training loads when reached via systematic progression are necessary for peak performance and also protective from injury. Conversely, periods following reduced training due to planned rest, tapering, or injury/ illness are a time of increased risk for an adverse event to occur. Optimizing competition performance requires careful management between training stimulus and recovery for positive adaptations to occur, while minimizing the risk of developing non-functional overreaching, injury and illness. Monitoring elite training programs is becoming increasingly scientific and analytical. The advent and greater accessibility of tools such as heart rate monitors, GPS, power measuring devices, and analytical software has led to an exponential increase in data collected from training, competition, and recovery. Despite this, the level of complexity and specificity of the monitoring system must be tailored to the requirements of the individual athlete. A trusting athlete-coach relationship is the foundation of any monitoring system in which training prescription is manipulated based on subjective feedback from the athlete and coach. The next level of monitoring involves integrating more objective quantification of training stimulus via measurement of external (e.g., power and pace), and internal (e.g., heart rate and blood lactate) loads. Finally, at the elite or Olympic level, athlete monitoring often involves a performance services team who provide specialized support to the athlete and coach. At this level novel tools or processes that measure specific physiological adaptions to training such as cardiac autonomic function, neuromuscular function, sleep efficiency and biochemical/hormonal/immunological are employed. Additionally, advanced data analytics is emerging as powerful component of training monitoring due to the immense volume of data now available. Integration, analysis and interpretation of data from each level of monitoring can then provide descriptive, diagnostic, predictive and prescriptive information. Despite the increasing volume and complexity of data available, one must remember that the primary objective of training monitoring remains collecting targeted and individualized information, provide efficient data analysis, interpretation and scientifically valid feedback to the coach and athlete.